G2019S LRRK2 mutation causing Parkinson's disease without Lewy bodies. Issue 6 (8th January 2007) - Gaig, Carles; Martí, María José; Ezquerra, Mario; Rey, Maria Jesús; Cardozo, Adriana; Tolosa, Eduardo
Abstract : The G2019S leucine-rich repeat kinase 2 gene ( LRRK2 ) mutation has been identified in a significant proportion of familial and sporadic cases of Parkinson's disease (PD). Until now, information on the neuropathological changes associated with the G2019S LRRK2 mutation has been sparse. We report a 77-year-old patient who presented with a 14 year history of PD but, unexpectedly, histopathological examination disclosed mild neuronal loss in the substantia nigra without α-synuclein, tau or ubiquitin cytoplasmic inclusions. A G2019S LRRK2 mutation was eventually detected. The present case confirms that clinical PD caused by G2019S mutations can be associated with non-specific nigral degeneration without Lewy bodies.